Reactive distillation process for the production of furfural using solid acid catalysts. Issue 3 (19th November 2014) - Metkar, Pranit S.; Till, Eric J.; Corbin, David R.; Pereira, Carmo J.; Hutchenson, Keith W.; Sengupta, Sourav K.
Abstract : A novel continuous reactive distillation process with solid acid catalysts is demonstrated for the production of furfural from synthetic and pre-hydrolysate liquor feeds containing xylose. Abstract : This paper presents a continuous reactive distillation process using solid acid catalysts to produce furfural from synthetic and real (pre-hydrolysate liquor (PHL) from wood chip digestion) feeds containing xylose. The reactive distillation process provides a unique advantage of immediate furfural separation from the reaction zone as it is formed, thus minimizing the formation of undesired by-products ( e.g., oligomers of furfural/humins) from subsequent furfural condensation reactions. A comprehensive experimental study was carried out using synthetic xylose feeds containing a mixture of pure xylose, water, and sulfolane as a solvent. Among various solid acid catalysts screened for their ability to produce furfural from dehydration of xylose, the zeolite H-mordenite (Si/Al = 10) gave the highest furfural yield (>75%). During this process, the aqueous feed was introduced at the top of the column, and xylose was dehydrated to furfural which was co-distilled with water out of the top of the column. The high-boiling sulfolane, with dissolved undesired byproducts, was collected at the bottom of the column. Steam-stripping was found to be helpful in effective separation of furfural from the reaction zone, thus further enhancing furfural yield. This study was extended to using authentic aqueous PHL feed. Salts present in this feed resulted in significant catalyst deactivation. Pre-treatment of the PHL feed with ion-exchange resin was found to be effective in achieving furfural yields of ∼75%. An in situ catalyst regeneration method was demonstrated successfully and resulted in achieving extended catalyst lifetime and furfural yield, similar to that obtained with synthetic xylose feeds.